1976
DOI: 10.1007/bf01927623
|View full text |Cite
|
Sign up to set email alerts
|

Tumor promoting constituent ofEuphorbia serrata L. latex

Abstract: Euphorbia serrata latex has initially ingenol-3-palmitate, which by action of silica gel is converted to ingenol-20-palmitate. The former is responsible for the irritant and cocarcinogenic activity of the latex on mouse ear and on mice back skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Fli-1 transactivating compounds are structurally related to diterpenes, a family of drugs including 12-O-tetradecanoylphorbol-13-acetate (TPA), which promotes tumorigenesis when applied to the skin [25, 26]. To determine their biological activity, leukemic cell lines expressing high or low levels of Fli-1 were treated with the compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Fli-1 transactivating compounds are structurally related to diterpenes, a family of drugs including 12-O-tetradecanoylphorbol-13-acetate (TPA), which promotes tumorigenesis when applied to the skin [25, 26]. To determine their biological activity, leukemic cell lines expressing high or low levels of Fli-1 were treated with the compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Biological investigations revealed that euphorbia factor L 5 (93) and compounds 139 and 140 are tumor promoters. 100,101 2.3.6 Other activities. Kansuiphorin A (94) showed antiviral activity and it is suggested that this compound prevents viral pneumonia in mice.…”
Section: Tiglianes †mentioning
confidence: 99%
“…238 In 1971, Adolf and Hecker showed that the carcinogenic activity in mice due to oil extracted from the seeds of E. lathyris L. resulted from the irritating activity of the esters of ingenol 7-hydroxy-lathyrol and a monoester of ingenol. 240 Previously, Upadhyay et al (1976) evaluated the latex extracted from E. serrata, from which ingenol-3-palmitate originated, which exhibited irritant and carcinogenic activities in an ear and dorsal skin test of NMRI mice. 241 Opferkuch and Hecker (1982) isolated compounds from E. ingens E. Mey.…”
Section: Ingenane/diterpenes Toxicities and Tumor Promotion Effectsmentioning
confidence: 99%